Adenoid squamous cell carcinoma of right gingivobuccal sulcus – A rare case report - Pande, Pankaj; Patil, Prakash Murigeppa; Bhalodia, Mihir J.; Savle, Jyotirling; Mulay, Himanshu (Asian Journal of Medical Sciences, 2014)
Oral cancer is the sixth most common malignancy in the world and third most common in southeast Asia. When it does occur, it is most commonly seen on the tongue or lip. Cancers of the gingivobuccal sulcus are uncommon and reported infrequently. Here we report a case of 35 years female diagnosed with adenoid squamous cell carcinoma of right gingivobuccal sulcus. Most of these cancers are locally advanced stage due to delay in presentation and ignorance of population. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10793 Asian Journal of Medical Sciences Vol.6(3) 2015 94-96